Marguerite by the lake : a novel - Carter, Mary Dixie (Minotaur Books, 2025)
"From Mary Dixie Carter comes an atmospheric, tense novel about the death of a glamorous garden designer, a widower trying to keep his secrets buried, and the beautiful young gardener who finds herself entangled in their lives. Marguerite Gray is a lifestyle icon known for her garden parties, high-end business ventures, and being the muse behind the famous Serge Kuhnert painting, Marguerite by the Lake. Her presence is overpowering, her taste, legendary. For the last few years, Phoenix has been the gardener on the famed Rosecliff grounds, home of the Gray family: Marguerite and her husband Geoffrey. Phoenix came from humble beginnings, and now she works hard to craft the landscape that underpins Marguerite's brand. When a storm threatens the launch party for Marguerite's latest book, it's Phoenix who spots the danger to the guests and rushes to Geoffrey's side to save him from a falling tree. Geoffrey is grateful-perhaps too grateful. Marguerite is . . . jealous. Phoenix senses the danger of being drawn deeper into their lives but can't resist the attention, becoming embroiled in an affair that could destroy her career. But soon after the affair begins Marguerite falls to her death, from the same high point at Rosecliff where she posed for Marguerite by the Lake. Now Phoenix has another secret, one that haunts her even as Geoffrey invites her to move into the manor with him. A secret that Detective Hanna and Marguerite's daughter--her spitting image--are circling closer and closer to. Phoenix tries to put it all behind her and find her rightful place at Rosecliff. But as every gardener knows, nothing stays buried forever"--